-x+6x-19x=-18x+40

Simple and best practice solution for -x+6x-19x=-18x+40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+6x-19x=-18x+40 equation:


Simplifying
-1x + 6x + -19x = -18x + 40

Combine like terms: -1x + 6x = 5x
5x + -19x = -18x + 40

Combine like terms: 5x + -19x = -14x
-14x = -18x + 40

Reorder the terms:
-14x = 40 + -18x

Solving
-14x = 40 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-14x + 18x = 40 + -18x + 18x

Combine like terms: -14x + 18x = 4x
4x = 40 + -18x + 18x

Combine like terms: -18x + 18x = 0
4x = 40 + 0
4x = 40

Divide each side by '4'.
x = 10

Simplifying
x = 10

See similar equations:

| y=3.90+0.05x | | 0.35=16x/1.4-x | | (0.35)/16x/1.4-x | | 16x/1.4/0.35 | | 9y-5=4y+5 | | (1/2)2^3-6 | | 25x+3=65x-13 | | 12x-x+9x=11x-180 | | 6x-2-5x=11 | | 7x(-x+6)= | | 11=6x-2-5x | | y+8=2y+4 | | 3x+5=-4x | | 0.5(-8p+1)=4p+1 | | 5+3n=40-4n | | 7x+2x=8x+16 | | -8(.2x+.4)-1.7=-.1 | | 5t-6=t^2 | | 10-4*3=3+13 | | 5x^2+6x=9 | | 10-4*4=4+13 | | 10-4*8=8+13 | | 20+.15x=50 | | 30+.10x=50 | | 30+.10x=20+.15x | | 7x+5=-7+3x+20 | | 6x+34+8x=14 | | 9a^2=30+39a | | 60=lwh | | 0=320x-x^2 | | 4600-(100+3x)=0 | | 7+4(3x-5)=9-3(2x+1) |

Equations solver categories